Infark Miokard Non-Segmen Elevasi ST pada Kasus Fraktur Terbuka Multipel: Laporan Kasus - Made Ratih Santi Devinta; I Gusti Agung Bagus Krisna Jayantika (Warmadewa University, 2025)
Myocardial infarction (MI) generally occurs due to coronary atherosclerosis. However, under certain circumstances, trauma can act as a trigger for MI. This case report discusses the occurrence of NSTEMI in a patient with multiple open fractures and explores several hypotheses that may contribute to the development of myocardial infarction in the setting of non-thoracic trauma. A 53-year-old man presented to the emergency department following a motorcycle accident. He was treated for multiple open fractures and developed a myocardial infarction on the first day of hospitalization, approximately 40 hours after the trauma. Electrocardiography (ECG) revealed no significant ST-segment changes, while high-sensitivity troponin I levels were markedly elevated at 609.5 ng/mL, and the hemoglobin level was 8.3 g/dL. The patient was co-managed with the cardiology team and received dual antiplatelet therapy (DAPT) and anticoagulation. The orthopedic procedure was postponed until hemodynamic stability was achieved. Myocardial infarction following an open fracture may occur due to rupture of an atherosclerotic plaque, an imbalance between myocardial oxygen supply and demand, and/or increased pro-inflammatory mediators resulting from the bone remodeling process or post-traumatic stress. Myocardial infarction in the setting of open fractures may result from atherosclerotic plaque rupture, oxygen supply–demand imbalance, and/or elevated pro-inflammatory mediators associated with bone remodeling or post-traumatic stress. Increased awareness of potential cardiovascular complications is essential, particularly in trauma patients with pre-existing cardiovascular risk factors.